Identifikasi Parameter Bod Dan Cod Dalam Air Limbah Pt. X Menggunakan Software Pemodelan Mike 21 - Firra Rosariawari; Ahmad Iqbal Addzikri (Prosiding ESEC, 2023)
This study aims to test the MIKE 21 Software model in predicting the distribution of COD andBOD parameters in PT. X East Java. Although not all water bodies that function as a meansof receiving liquid waste are used by humans (residents) to bathe or drink, it still refers toAnnex VI of PP RI Number 22 of 2021 concerning National Water Quality Standards. Thisstudy aims to determine the parameters of BOD and COD produced by PT. X food industryuses MIKE 21 modeling software. Monitoring was carried out at 4 points with a distancedifference of 300m per point. The results obtained were that the simulation of BOD distributionwas carried out for 30 days using the maximum value concentration of waste discharge activity(30 mg / L) for the front river and 85 mg / L for the back river, while the simulation of CODdistribution simulation was carried out for 30 days using the maximum value concentration ofwaste discharge activity (30 mg / L) for the front river and 85 mg / L for the back river.